The Rat Fallopian Tubes after Erythropoietin Process - Τsompos, C; Panoulis, C; Triantafyllou, A; Zografos, CG; Gerakis, E; Gerakis, S; Papalois, A (Free Radicals and Antioxidants)
Aim: The capability of erythropoietin (EPO) as antioxidant is exported by the results of 2 preliminary studies, totally evaluating 4 histologic variables of endosalpingeal edema (EE) and oviductal congestion (OC) of the first one and endosalpingeal karyorrhexis (EK) and salpingitis (S) of the other one. Materials and Methods: The antioxidant capability was evaluated upon the 60th reperfusion min (for groups called A and C) and upon the 120th reperfusion min (for groups called B and D). The groups A and B were placebo ones, whereas the groups C and D included EPO as antioxidant. Results: The first pillar study showed that EPO has an oxidant non-significant potency for EE and OC together (p-values=0.5971); grade: “without lesions” alterations 0.0363636 [-0.1017439 - 0.1744712]. The second pillar study showed also an oxidant non-significant potency for EK and S; grade: “without lesions” alterations 0.0090909 [-0.0339659 - 0.0521478] (p-values=0.6715). The 2 above studies were added trying to calculate a common diagnostic value for all the four variables. Conclusion: EPO as antioxidant is a significant recessing agent for the total of the 4 histologic variables; grade: “without lesions” alterations score 0.0136364 [-0.0887489+0.0614762] (p-value=0.7153).
Keywords: Ischemia; Erythropoietin; Endosalpingeal edema; Oviductal congestion; Endosalpingeal karyorrhexis; Salpingitis; Reperfusion